La collaboration entre chercheuse et praticiens dans un groupe de codéveloppement professionnel - Josianne Caron; Liliane Portelance (Éducation et Socialisation)
Student teachers struggle to relate knowledge issued from research (KFR) to that from teaching practice (Altet, 2010). However, as well as knowledge issued from practices, KFR are resources with potential for use (Perrenoud, 2001). Student teachers need training to exploit the KFR in order to mitigate the shock when they are confronting the reality of the school, and they ask for their cooperating teachers support (Desbiens, Borges and Spallanzani, 2012). The latter have few opportunities to meet and exchange and they have few scientific references to guide their actions with the student teacher (L’Hostie, Monney and Nadeau-Tremblay, 2013). Their needs have been identified (Caron and Portelance, 2017). Those needs have been taken into account in a collaborative research within a professional co-development group (Payette and Champagne, 2010). In the following text, the emphasize is on the collective identification of the practices and the intentions of use of KFR by a associate teacher in her reflective supervision of a student teacher.